High risk of metabolic syndrome after delivery in pregnancies complicated by gestational diabetes. (April 2019) - Shen, Yun; Li, Weiqin; Leng, Junhong; Zhang, Shuang; Liu, Huikun; Li, Wei; Wang, Leishen; Tian, Huiguang; Chen, Jinbo; Qi, Lu; Yang, Xilin; Yu, Zhijie; et al.
Abstract: Aims: To investigate the risk of postpartum metabolic syndrome in women with GDM compared with those without GDM in a Chinese population. Methods: Tianjin GDM observational study included 1263 women with a history of GDM and 705 women without GDM. Multivariate logistic regression was used to assess risks of postpartum metabolic syndrome between women with and without GDM. Postpartum metabolic syndrome was diagnosed by two commonly used criteria. Results: During a mean 3.53 years of follow up, 256 cases of metabolic syndrome were identified by using the NCEP ATPIII criteria and 244 cases by using the IDF criteria. Multivariable-adjusted odds ratios of metabolic syndrome in women with GDM compared with those without GDM were 3.66 (95% confidence interval [CI] 2.02–6.63) for NCEP ATPIII criteria and 3.90 (95% CI 2.13–7.14) for IDF criteria. Women with GDM had higher multivariable-adjusted odds ratios of central obesity, hypertriglyceridemia, and high blood pressure than women without GDM. The multivariable-adjusted odds ratios of low HDL cholesterol and hyperglycemia were not significant between women with and without GDM, however, the multivariable-adjusted odds ratio of hyperglycemia became significant when we used the modified criteria. Conclusions: The present study indicated that women with prior GDM had significantly higher risks for postpartum metabolic syndrome, as well as its individual components.